Oxidative Stress and Inflammation as Targets for Novel Preventive and Therapeutic Approches in Non Communicable Diseases - Nediani, Chiara; Giovannelli, Lisa (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Non-communicable diseases (NCDs) are chronic diseases that include most ageing-related diseases, representing the main cause of death and disability in the general population. Inflammation and oxidative stress are common features in NCDs, responsible for the cell, tissue, and organ damage that contributes to the progression of these diseases. They may be also key targets for the development of novel preventive and therapeutic strategies. This Special Issue includes 14 peer-reviewed papers, including 12 original research papers and 2 reviews. Together, they represent the most recent progress in the field of several degenerative disorders, aiming to establish specific biomarkers, detailing the pathogenesis and the evolution of these diseases, making a correct diagnosis, and opening up new therapeutic strategies. Of relevance, many studies report the beneficial effects of natural compounds, derived from several plants, leaves, and fruits; their antioxidant and anti-inflammatory properties suggest their use as a dietary supplement for prevention and/or complement to standard therapies. Special thanks to all authors and reviewers for their valuable contributions and constructive suggestions and to the publishing team of Antioxidants for their help in compiling this Special Issue.